Emerging role of exosome-derived non-coding RNAs in tumor-associated angiogenesis of tumor microenvironment - Duan, Sai-Li; Fu, Wei-Jie; Jiang, Ying-Ke; Peng, Lu-Shan; Ousmane, Diabate; Zhang, Zhe-Jia; Wang, Jun-Pu (Frontiers in Molecular Biosciences, 2023)
The tumor microenvironment (TME) is an intricate ecosystem that is actively involved in various stages of cancer occurrence and development. Some characteristics of tumor biological behavior, such as proliferation, migration, invasion, inhibition of apoptosis, immune escape, angiogenesis, and metabolic reprogramming, are affected by TME. Studies have shown that non-coding RNAs, especially long-chain non-coding RNAs and microRNAs in cancer-derived exosomes, facilitate intercellular communication as a mechanism for regulating angiogenesis. They stimulate tumor growth, as well as angiogenesis, metastasis, and reprogramming of the TME. Exploring the relationship between exogenous non-coding RNAs and tumor-associated endothelial cells, as well as their role in angiogenesis, clinicians will gain new insights into treatment as a result.